Psychosocial volunteer support for older adults with cognitive impairment: development of MyCare Ageing using a codesign approach via action research - Dave Vicary; Velandai K Srikanth; Darshini Ayton; Renée O'donnell; Helen Skouteris; Catherine Bateman; Chris Moran; Julie Lustig; Jane Banaszak-Holl; Peter Hunter; Elizabeth Pritchard; Heather Morris; et al. (BMJ Open)
Background and objectives Older adults with cognitive impairment are vulnerable to frequent hospital admissions and emergency department presentations. The aim of this study was to use a codesign approach to develop MyCare Ageing, a programme that will train volunteers to provide psychosocial support to older people with dementia and/or delirium in hospital and at home when discharged from hospital.Setting Melbourne, Victoria, Australia.Research design This study adopts an action research methodology. We report on two co-design workshops with keystakeholders: Workshop 1: identification of components from three existing programmes to inform the development of the MyCare Ageing program logic and, Workshop 2: identification of implementation strategies.Participants The key stakeholders and workshop participants included clinicians (geriatricians, nurses and allied health), hospital staff (volunteer coordinators and hospital executives), Baptcare staff, a consumer, researchers and implementation experts and project staff.Results Workshop 1 identified the components from three existing programmes—the Volunteer Dementia and Delirium Care programme, Home-Start and MyCare for inclusion in MyCare Ageing. In workshop 2, the p implementation plan was developed taking into consideration hospital-specific processes, training and support needs of volunteers and safety and risk management processes.Discussion and conclusion The codesign process was successfully applied to develop the MyCare Ageing programme to provide volunteer support to patients with dementia and/or delirium in hospital and their transition home. MyCare Ageing is an innovative programme that meets an identified need from hospitals and consumers to support patients with dementia and/or delirium to improve psychosocial outcomes on discharge from hospital.